An unexplained overlap betweenÂ SophistÂ 232b1-236d4 and RepublicÂ X: The case of the sophist as a painter - Zucchetti, Nicholas (Revista Archai, 2020)
Although most scholars agree that the lexicon of Sophist 232b1-236d4 is similar to that of Republic X, they leave undetermined whether they are theoretically compatible. Notably, both dialogues elucidate the art of imitation through the metaphor of the painter who deceives his pupils through Ï†Î±Î½Ï„Î¬ÏƒÎ¼Î±Ï„Î±. I argue that Plato’s conception of imitation of the Republic is not only consistent with that presented in the Sophist, but also importantly integrates it.